A General and Mild Catalytic α‐Alkylation of Unactivated Esters Using Alcohols1. (30th January 2015) - Guo, Le; Ma, Xiaochen; Fang, Huaquan; Jia, Xiangqing; Huang, Zheng
Abstract Catalytic α‐alkylation of esters with primary alcohols is a desirable process because it uses low‐toxicity agents and generates water as the by‐product. Reported herein is a NCP pincer/Ir catalyst which is highly efficient for α‐alkylation of a broad scope of unactivated esters under mild reaction conditions. For the first time, alcohols alkylate unactivated α‐substituted acyclic esters, lactones, and even methyl and ethyl acetates. This method can be applied to the synthesis of carboxylic acid derivatives with diverse structures and functional groups, some of which would be impossible to access by conventional enolate alkylations with alkyl halides.